2017
DOI: 10.1017/s0007114517000277
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fibre additions to flatbread flour mixes for reducing post-meal glucose and insulin responses in healthy Indian subjects

Abstract: The incidence of type 2 diabetes mellitus (T2DM) is increasing worldwide, including in developing countries, particularly in South Asia. Intakes of foods generating a high postprandial glucose (PPG) response have been positively associated with T2DM. As part of efforts to identify effective and feasible strategies to reduce the glycaemic impact of carbohydrate-rich staples, we previously found that addition of guar gum (GG) and chickpea flour (CPF) to wheat flour could significantly reduce the PPG response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 64 publications
(93 reference statements)
2
28
0
1
Order By: Relevance
“…We evaluated our workflow on defined dilutions of 13 C-enriched metabolites in human plasma, and determined reproducibility, accuracy, and detection limits in this matrix. The applicability of the workflow was further demonstrated on time-resolved postprandial human plasma samples from three subjects that consumed 13 C-enriched wheat bread (2% of U 13 C wheat flour) generated in the course of a nutritional intervention study [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated our workflow on defined dilutions of 13 C-enriched metabolites in human plasma, and determined reproducibility, accuracy, and detection limits in this matrix. The applicability of the workflow was further demonstrated on time-resolved postprandial human plasma samples from three subjects that consumed 13 C-enriched wheat bread (2% of U 13 C wheat flour) generated in the course of a nutritional intervention study [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the Applicability of the workflow on plasma from a nutritional intervention study , we obtained plasma samples collected over a 360 min time frame from three subjects that consumed wheat bread with 2% of the wheat flour substituted with fully 13 C-labeled wheat flour [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…[ 112 ] Fortification of humble Indian dishes with fibre-rich alternatives, for example adding soluble fibre in the form of oats in upma or improving the glycaemic quality of Indian flatbreads (rotis or chapattis) by adding wheat flour with soluble viscous fibres and legume flour have shown favourable outcomes on the lipid profile and postprandial glucose and insulin responses in T2DM patients. [ 113 114 115 116 ] Sugar and sugar-sweetened beverages increase the dietary GL. Overall, the consumption of total sugar (25.0 kg/capita) among Indians exceeds the average global annual per capita consumption (23.7 kg).…”
Section: R Ationale and E Videncementioning
confidence: 99%
“…[ 141 ] In randomized, cross-over study in 56 healthy Indian participants, consumption of flatbreads with addition of fibrous flour such as chickpea (15%) and guar gum (3% or 4%) to wheat flour significantly reduced postprandial glucose (p<0.01) and postprandial insulin (p<0.0001) when compared with flatbreads made from control flour (100% wheat flour). [ 113 ] In a dietary assessment study in urban Asian Indians with T2DM, low consumption of dietary fibres (<29 g/day) was associated with higher prevalence of hypercholesterolemia (p=0.01) and higher LDL (p=0.001) than individuals with greater median intake of fibres. [ 142 ] In a randomized study, daily consumption of 3 g of soluble fibre from 70 g of oats in form of porridge or upma for 28 days in mildly hypercholesterolaemic Asian Indians was associated with significant reduction in serum cholesterol (p<0.02) and LDL (p<0.04) versus control group (routine diet).…”
Section: R Ationale and E Videncementioning
confidence: 99%
“…In addition, legume flours, such as chickpea flour (CPF), are known to give a lower PPG response than wheat flours (14) . We observed that viscous guar gum (GG) added to flatbread flour in combination with CPF dose dependently lowered PPG and PPI responses (15,16) . It is assumed that viscous gums mainly affect PPG by reducing rates of glucose absorption (17)(18)(19)(20) , but testing this hypothesis would require a determination of glucose fluxes.…”
mentioning
confidence: 98%